Placebo‐controlled Randomized Clinical Trial on the Immunomodulating Activities of Low‐ and High‐Dose Bromelain after Oral Administration – New Evidence on the Antiinflammatory Mode of Action of Bromelain. (20th April 2012) - Müller, Silke; März, Reinhard; Schmolz, Manfred; Drewelow, Bernd; Eschmann, Klaus; Meiser, Peter
<x xml:space="preserve">Abstract</x> Bromelain has been used for treatment of inflammatory diseases for decades. However, the exact mechanism of action remains poorly understood. While in vitro investigations have shown conflicting effects on the release of various cytokines, no in vivo data were available. In this study, the effects on inflammation‐related cytokines of two doses of bromelain were tested in a single dose placebo‐controlled 3 × crossover randomized clinical trial. Cytokine circadian profiles were used to investigate the effects of bromelain on the human immune system by using stimulated whole‐blood leukocytes. The effects seen in these cultures demonstrated a significant shift in the circadian profiles of the Th1 cell mediator interferon gamma (IFNγ; p < 0.043) after bromelain 3000 FIP (Fédération Internationale Pharmaceutique) units, and trends in those of the Th2‐type cytokine IL‐5 as well as the immunosuppressive cytokine interleukin (IL)‐10. This suggests a general effect on the antigen‐specific (T cell) compartment of the human immune system. This is the first time that bromelain has been shown to modulate the cellular responses of lymphocyte after oral use. It is postulated that the immunomodulating effect of bromelain observed in this trial is part of its known antiinflammatory activities. Further investigations will be necessary to verify the relevance of these findings to a diseased immune system. Copyright © 2012 John Wiley & Sons, Ltd.